Stress and Coping: Considering the Influence of Psychological Strengths on the Mental Health of At-Risk South African Adolescents. Issue 1 (2nd January 2021) - Harrison, Carmen; Loxton, Helene; Somhlaba, Nceba Z.
ABSTRACT: In South Africa, many adolescents are affected by socio-economic adversity, which increases their susceptibility to experiencing stress that negatively affects their mental health. The synthesis of international literature has identified the psychological strengths (that include perceived social support, self-esteem and resilience) as having a protective effect on the mental health of at-risk adolescents who experience stress. Against this background, we argue that psychological strengths may assist South African adolescents in coping with stressors and may mediate the impact of stress on the mental health of adolescents living in conditions of socio-economic adversity. Given that this remains an under-researched area in the South African context, we also highlight the need for South African research that prioritizes the exploration of factors mitigating the experience of stress for adolescents. We also posit that such research should have significant implications for mental-health policy, practice, mental-health promotion and the prevention of mental disorders. We believe that such scholarly inquiries would be central to the intervention strategies aimed at preventing or "containing" the scourge of poverty-induced psychological distress in South African youth.